Comprehensive look at the photochemistry of Tolane - Krämer, Maximilian; Bunz, Uwe H. F.; Dreuw, Andreas (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2017)
Diphenylacetylene (tolane) exhibits a rich photochemistry that depends on the relative orientation of the phenyl rings and the external conditions. Here, state-of-the-art quantum chemical methods based on the algebraic diagrammatic construction scheme for a polarization propagator of second order are employed to investigate the luminescence properties of tolane and its derivatives. It is explained why different derivatives of tolane exhibit different absorption but practically identical fluorescence spectra, why the fluorescence quantum yield and the population of a “dark” state are temperature-dependent, and why initially twisted tolanophanes phosphoresce in glassy media at 77 K while planar ones do not.